Covid-19 Infection Is A Significant Risk Factor For Death In Patients Presenting With Acute Cholecystitis : A Secondary Analysis Of The Choco-w Cohort Study. - Belinda De Simone; Fikri M. Abu-Zidan; Lucienne Kasongo; Ernest E. Moore; Mauro Podda; Massimo Sartelli; Arda Isik; Miklosh Bala; Raul Coimbra; Zsolt J. Balogh; Kemal Rasa; Francesco Marchegiani; et al. (Biomedcentral (BMC), 2025)
Index by WOS (Tier 1)